Implementation of IPv6 using 6RD Method on Power Line Communication Network - Siregar, Yasir Al-Farizi; Suhatman, Rahmat (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The development of computer network technology is rapidly advancing in response to society's increasing demand for network services. Currently, the most widely used network protocol is IPv4, but it has some limitations. To address these limitations, a new network protocol, IPv6, has been developed. More and more new network devices are using IPv6 as their IP address, while many existing technologies and internet devices still use IPv4. Therefore, a mechanism is required to transition from IPv4 to IPv6. The 6RD tunneling method is used in Power Line Communication networks to connect two or more network devices using electrical wiring as a data transmission medium. The Power Line is equipped with a charger for a laptop and a drill, creating a load to test the performance of the Quality of Service(QoS) with the throughput parameter. The measured Rerate throughput upload was 11800 Kbit/s without any additional electrical load, 9377.8 Kbit/s with a laptop charger as an additional load, and 6082.2 Kbit/s with a drill as an additional load. The Rerate throughput download was 8098.8 Kbit/s without any additional electrical load, 7782.8 Kbit/s with a laptop charger as an additional load, and 5996 Kbit/s with a laptop charger and a drill as additional loads. With this transition mechanism, IPv4 can communicate with IPv6, allowing for more efficient network communication.